2003
DOI: 10.1002/mds.10474
|View full text |Cite
|
Sign up to set email alerts
|

Fast micrographia and pallidal pathology

Abstract: Fast micrographia differs from the customary micrographia of Parkinson's disease and appears to be characteristic of patients with pallidal lesions. © 2003 Movement Disorder Society

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…Regarding the nature of parkinsonism, it appears that, in these published cases, axial motor problems (gait and speech disorder with possible freezing and postural instability) seemed to dominate over brady/akinesia (defined mainly by rapid alternating (distal) limb movements), rigidity, and tremor of the limbs (table 3). This was also the case with our patient, who had a speech problem, ''fast micrographia'', 13 and impaired postural reflexes, but no distal limb akinesia or tremor. However, the clinical picture of parkinsonism of our case differed from that of typical PD, as the main clinical findings in PD are rest tremor, distal bradykinesia, and limb rigidity.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Regarding the nature of parkinsonism, it appears that, in these published cases, axial motor problems (gait and speech disorder with possible freezing and postural instability) seemed to dominate over brady/akinesia (defined mainly by rapid alternating (distal) limb movements), rigidity, and tremor of the limbs (table 3). This was also the case with our patient, who had a speech problem, ''fast micrographia'', 13 and impaired postural reflexes, but no distal limb akinesia or tremor. However, the clinical picture of parkinsonism of our case differed from that of typical PD, as the main clinical findings in PD are rest tremor, distal bradykinesia, and limb rigidity.…”
Section: Discussionsupporting
confidence: 79%
“…However, alternate supination and pronation of the arms revealed a dramatic deficit with rapid breakdown of rhythm, timing, and amplitude and fatigue over 5-10 repetitions. On writing there was ''fast micrographia'', 13 so that although the size of his writing was extremely small, its speed was normal. He could, however, use his hands normally for doing up buttons, tying laces, and pressing computer keys.…”
Section: Case Descriptionmentioning
confidence: 99%
“…[4] ‘Handwriting is microscopic from the outset, does not (indeed cannot) become progressively smaller, is accomplished at (astonishingly) normal speed, and does not fatigue. This micrographia can be so marked as to resemble a straight line, so that even the patients are often unable to read what they have written.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the degree of micrographia in Parkinson’s disease is usually proportional to the degree of decrement in rate and amplitude of alternating finger movements in the dominant hand, many patients with fast micrographia have completely normal alternating finger movements’. [4] The authors have observed fast micrographia in case of progressive supranuclear palsy and acquired bilateral lesions of the globus pallidus. [4] They have proposed that ‘the presence of fast micrographia, usually unaccompanied by significant fatiguing or decrement of alternating finger movements, should be considered a useful clinical pointer to the possibility of pallidal pathology’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation